Half circle position for arc cracks in half plane - Elfakhakhre, Nawara R. F.; Nik long, Nik Mohd Asri; Eshkuvatov, Zainidin K. (IOP Publishing, 2018)
In this paper, the problem of arc cracks that lie in the boundary of half circle in an elastic half plane is investigated. The complex potential variables with free traction boundary condition is used to formulate the problem into a singular integral equation. The singular integral equation is solved numerically for the unknown distribution dislocation function with the help of curve length coordinate method. The numerical results have shown that our results are in good agreement with the previous works. Stress intensity factors for different cracks position are presented .